ΑΠΟ ΤΗΝ «ΞΕΝΗ ΠΑΙΔΟΚΤΟΝΟ» ΤΟΥ ΕΥΡΙΠΙΔΗ ΣΤΗΝ ΑΝΕΛΕΗΤΗ ΣΑΤΙΡΑ ΤΗΣ «ΝΕΑΣ ΓΥΝΑΙΚΑΣ» ΤΩΝ ΦΡΑΝΚΑ ΡΑΜΕ ΚΑΙ ΝΤΑΡΙΟ ΦΟ [FROM THE «FOREIGN INFANTICIDE» OF EURIPIDES TO THE MERCILESS SATIRE OF THE «NEW WOMAN» BY FRANCA RAME AND DARIO FO] - Kosmopoulou, Despina (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
The ancient Greek tragedy has offered the world theatre multiple archetypes, which have been used from antiquity to the present time, either modified or adapted, or even as sources of inspiration for the creation of new theatrical works. Medea is the archetype of the «foreign infanticide», who kills her children in order to claim back her unfaithful husband, who chose to marry a younger and more politically powerful wife. Medea symbolizes the woman, who gives a political speech in an era, women did not have such rights. Euripides in his tragedy touches on a number of female issues that troubled the female audience of his time, such as dowry, infidelity and divorce. The reception of ancient Greek tragedy by 20th and 21st century dramatists render the archetypes in different ways and especially often. In the context of the revolutionary-feminist theatre, Dario Fo and Franca Rame create a Medea with a revolutionary nature, who is troubled by hot female issues of her time, which expresses with an equally interesting political discourse.